LA ETICA DEL CAPITALISMO / COMENTARIO DE LA ETICA DEL CAPITALISMO / JAMES M. BUCHANAN ; TR. RICARDO FERNANDEZ CRESPO - Koslowski, Peter (EMPRESA Y HUMANISMO ;, 1997)
TRADUCCION DE: ETHIK DES KAPITALISMUS